AJIC Issue 20, 2017-Full Issue-Print-on-Demand Version - (:unkn) unknown (My University, 2017)
This AJIC Issue 20 provides a three-article Focus Section on Cybersecurity, and articles and thematic reports on: the future of SADC digital economy regulation; development of a first aid smartphone app; development of a communication strategy to address violence against children; the potential use of drones in land-mapping; and uncertainties in the legalities of e-commerce transactions.